Intravascular Leiomyomatosis of the Uterus: A Report of Two Cases - Çağlar, Bahar; Ovalı, Sema; Kır, Gözde (Gynecology Obstetrics & Reproductive Medicine, 2011)
Two cases of intravascular leiomyomatosis (IVL) of the uterus, a rare benign smooth-muscle tumor, are described. A preoperative diagnosis of IVL was not introduced in the patients, both of which presented with a pelvic mass with the presumptive diagnosis of leiomyoma. Surgical exploration confirmed the presence of uterine mass and none of the cases showed extra-uterine extension. Histological examination demonstrated a fascicular pattern of bland spindle-shaped smooth-muscle cells,which extended to veins inside the myometrium. The present diagnosis was confirmed by immunohistochemical stain for desmin and CD 34. Despite their histological benignity, these lesions have tendency to metastasize and are closely related to the conditions called ‘benign metastasizing leiomyoma’ and ‘intracaval mass and cardiac extension’. The primary treatment of IVL is hysterectomy and excision of any extrauterine tumor, when technically feasible. Anti-estrogenic therapy has been suggested as potentially useful in controlling of unresactable tumor. Regarding recent data, the follow-up must be long and periodic postoperative ultrasonic or magnetic resonance imaging studies may be useful in detecting growth of residual intravascular tumor.